2018
DOI: 10.4103/ua.ua_194_17
|View full text |Cite
|
Sign up to set email alerts
|

A case of splenogonadal fusion accompanied by accessory spleen in a 4-year-old boy

Abstract: Splenogonadal fusion (SGF) is a rare benign malformation in which spleen is aberrantly attached to the gonads or mesonephric derivatives. This entity often presents with scrotal mass, inguinal hernia, or cryptorchidism. Herein, we report our experience with a boy who presented with a scrotal enlargement which later turned out to be SGF. Moreover, an accessory spleen was unexpectedly found in the left inguinal canal. To the best of our knowledge, this is the first report of SGF and accessory spleen in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In a case of SGF presenting as a testicular tumor, it was reported that dynamic observation was continued only after a biopsy of the mass. Subsequently, the diagnosis of discontinuous splenogonadal fusion was made ( 18 ). A fibrous capsule can be clearly observed between the testes and the spleen in both the continuous and the discontinuous types.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of SGF presenting as a testicular tumor, it was reported that dynamic observation was continued only after a biopsy of the mass. Subsequently, the diagnosis of discontinuous splenogonadal fusion was made ( 18 ). A fibrous capsule can be clearly observed between the testes and the spleen in both the continuous and the discontinuous types.…”
Section: Discussionmentioning
confidence: 99%
“…The accessory spleen is caused by the fusion failure of the splenic anlage located in the dorsal mesogastrium in the fth week of fetal life [4] or developed from the deciduous part of the main spleen [5].…”
Section: Discussionmentioning
confidence: 99%